KUALITAS LAPORAN KEUANGAN PEMERINTAH PUSAT : TELAAH STUDI EMPIRIS - Kania Azizah, (2022)
The purpose of this study is to tanalysis and prove empirically the effect of applying accrual-based government accounting standards, human resource competence, and internal control to the quality of financial reports. The population used in this study is the Ministry of Agriculture, where the Ministry of Agriculture is the one who gets the WTP opinion from the BPK apart from other ministries so that it can be used as a population that can be researched and the sample used is the staff preparing financial statements at the Defense Agency Work Unit. Food consisting of 50 respondents using purposive sampling. Data analysis using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results obtained in this study can be concluded if the application of accrual-based government accounting standards and internal control has a significant effect on the quality of financial reports. Competence of human resources has no effect on the quality of financial reports.